Listening for/as presence: religious mediation of a Sufi ritual in the time of COVID-19 - Othman, Muhammad Lutfi Bin (Religion, 2022)
Every week in the time before COVID-19, the members of the Shadhili Sufi order in Singapore convened in their lodge to participate in a ritual of sound and movement called the hadra. In March 2020, Singapore's lockdown measures brought these ritual movements to a stop. In response, the group started participating in online gatherings, sacrificing the affective dimensions of their ritual. This article captures this transformation, focusing on the sensorial challenges that these Sufis were faced with due to the failure of technology to translate the atmospheric elements of their practice and how listening became the focus of their ritual engagement online. The article argues that these Sufis demonstrate that research in the sensory, embodied, and mediated elements of religious experiences need to take into consideration the spiritual dispositions of religious practitioners as spiritual dispositions can go past technological dysfunctions and make the external elements of worship internally effective.